Causes of death among hospitalized children under 5 years of age in Sulaymani Pediatrics Teaching Hospital (Iraqi Journal of Medical Sciences, 2020)
Back ground: Knowledge about the causes ofdeath in children is important to evaluatehealth system progress and provide what isneeded for an efficient design of health caredelivery system.Objective: To find out the main causes ofdeath in children under 5years & evaluate theeffects of different variables like: age, gender,body weight, residency, and months of year forthe causes of death.Patient& Method: This is a retrospective studywhich was carried out in order to find out themain causes of death among admitted childrenyounger than 5 year in Sulaymani PediatricsTeaching Hospital for the period of 5 yearsfrom of January 1st 2001 to December 31st2005 included. The total numbers of admittedcases was 137,739 out of which 1455 had died.We obtained the information from case files ofthe deceased patients.Results: The incidence of death amongadmitted patients was (1.06%), the rate washigher in male gender (59.3%), while in femaleit was (40.7 %), with a P-value of
Keywords: mortality rate; death cause